2012
DOI: 10.1111/j.1399-3054.2012.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cell walls and intracellular contents in supercooling capability of xylem parenchyma cells of boreal trees

Abstract: The supercooling capability of xylem parenchyma cells (XPCs) in boreal hardwood species differs depending not only on species, but also season. In this study, the roles of cell walls and intracellular contents in supercooling capability of XPCs were examined in three boreal hardwood species, Japanese beech, katsura tree and mulberry, whose supercooling capability differs largely depending on species and season. XPCs in these species harvested in winter and summer were treated by rapid freezing and thawing (RFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Recent studies have indicated that fluctuation of the temperature limit of supercooling in XPCs is influenced by intracellular substances in XPCs (Kasuga et al 2006;Kasuga et al unpublished). Supercooling capability of XPCs in beech is significantly reduced when the protoplasts are broken and the spaces within cell walls (previously occupied by protoplasts) are substituted with distilled water, suggesting an important role of original protoplast contents in supercooling (Kasuga et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that fluctuation of the temperature limit of supercooling in XPCs is influenced by intracellular substances in XPCs (Kasuga et al 2006;Kasuga et al unpublished). Supercooling capability of XPCs in beech is significantly reduced when the protoplasts are broken and the spaces within cell walls (previously occupied by protoplasts) are substituted with distilled water, suggesting an important role of original protoplast contents in supercooling (Kasuga et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Supercooling capability of XPCs in beech is significantly reduced when the protoplasts are broken and the spaces within cell walls (previously occupied by protoplasts) are substituted with distilled water, suggesting an important role of original protoplast contents in supercooling (Kasuga et al 2006). It has also been shown that expression of some genes (Takata et al 2007), accumulation of some proteins (Arora et al 1992;Welling and Palva 2006) and accumulation of soluble sugars (Kasuga et al 2007a) are related to fluctuation of supercooling capability in XPCs, although the roles of changes in these components in supercooling are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that artificial release of intracellular substances from XPCs significantly reduced supercooling capability in beech XPCs [13]. It has also been reported that the fluctuations of supercooling capability in XPCs are associated with changes in expression of many genes in larch [20], changes in accumulation of many proteins in several trees [5] and changes in accumulation of soluble carbohydrates in birch [9], although the direct roles of these physiological changes in deep supercooling of XPCs remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Like hinokitiol, the materials with anti-ice nucleation activity play an important role of deep supercooling in the xylem parenchyma cells of coniferous trees Kasuga et al, 2006 . Moreover, four kinds of flavonol glycosides with anti-ice nucleation activity have an important role in supercooling in the xylem parenchyma cells of katsura trees Cercidiphyllum japonicum Kasuga et al, 2008 .…”
Section: The Preparation Of the Extract From Coffee Refusementioning
confidence: 99%